Criminal Protection for the Scientific Certificates in the UAE Law : A Comparative Analytical Study - Monajjed, Manal (Journal of Legal Sciences, 2023)
At present, a scientific certificate has great importance as an indicator of the level of the educational qualification of a person, and a criterion on the basis of which job appointments are made. The title is granted by the scientific certificate. The status of the scientific certificate has had a dual effect. On the one hand, it encouraged persons to pursue educational attainment in order to obtain the highest scientific degrees and the associated moral and material advantages, and on the other hand. It prompted some to seek scientific degrees by any means or method and at any price in order to benefit from these advantages. This situation led to the emergence of unlicensed and fake universities that do not have a real presence on real life. Such universities award academic degrees with the highest grades in an exchange of sums of money. Of course, there are those who would pay money to obtain these scientific certificates without the slightest effort or fatigue. The legislator in the United Arab Emirates was cautious to the danger of this phenomenon., Since the UAE is one of the most attractive places for work, it issued Decree-Law No. (9) of 2021 banning the use of scientific certificates issued by unlicensed entities. This study aims to define this phenomenon and shed light on the provisions of the Decree-Law No. (9) of 2021 referred to above, to determine the extent of its adequacy to eliminate the illegal academic degrees.